Place attachment and rural youth's perceptions on rice field activities : the case of three homestays in Kedah / Puteri Yuliana Samsudin, Nor Zarifah Maliki and Suraiyati Rahman - Samsudin, Puteri Yuliana; Maliki, Nor Zarifah; Rahman, Suraiyati (2018)
Homestay programme is one of the main subjects in maintaining the cultural activities in tourism. Homestay programme is a form of community-based tourism that offers tourists and local communities to experience the local lifestyle and heritage culture. However, rapid urbanization has resulted in replacing the traditional components with modern components. This has caused facing reduction of definition and attachment in traditional places such as rice field. Realizing that youth plays an essential part in homestay programme, this paper tends to explore rural youth's perception of rice field activities in homestay programme. The perceptions include youth's knowledge, experience, and values on rice field activities. This paper highlights the concept of place attachment and provides an understanding the idea of homestay programme and focuses on homestay programme which has the rice field settings and offers rice field activities. The study has chosen three homestays in Kedah as a case study. The homestay programmes are Homestay Kg. D' Belimbing, Homestay Kg. Jeruju and Homestay Kg. Pantai Jamai, Kedah. It is hoped that this will further provide suggestions for future research.